Nilai-Nilai Pendidikan Islam Ahlus Sunnah wal Jamaah (Aswaja) dalam Kumpulan Cerpen Santri Bejo Menantu Kyai - Sofyaningrum, Rosita; Maulana, Ahmad Irham (JURNAL ISLAM NUSANTARA, 2022)
This research aims is to analyse and identify the values of Islamic Education of Ahlus Sunnah wal Jamaah (Aswaja) contained in a collection of short stories entitled Santri Bejo Menantu Kyai. The research method used in this research is a qualitative descriptive method with an interpretative approach. The data used in this research are written data in the form of quotation from the short stories related to the characteristics of Ahlus Sunnah wal Jamaah in the collection of short stories entitled Santri Bejo Menantu Kyai. The data source on this research is the collection of short stories entitled Santri Bejo Menantu Kyai. The data collection technique used in this research is the read- and- note technique. The data analysis technique employs a character approach by examining the content and implied purposes within the literary work, interoperating the values of Ahlus Sunnah wal Jamaah. The research findings indicates that the values of Ahlus Sunnah wal Jamaah in the collection of short stories entitled Santri Bejo Menantu Kyai encompass five attitudes. These attitudes are i’tidal which means take the truth path, tasawuth which means acting justly and to strike a balance; tawazun which means maintaining balance in actions (by doing deliberation); tasamuh which means having tolerance, mutual respect, and appreciate differences; amar ma’ruf nahi munkar which means enjoining what is good and forbidding what is evil.